Návrh na rozšíření marketingových činnosti firmy - Dítě, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Cílem této diplomové práce je návrh na rozšíření marketingových činností firmy. Práce se skládá z teoretické , analytické a praktické části. Na základě zjištění z analýzy jsou v praktické části formulovány konkrétní návrhy na rozšíření marketingových činností. Tyto návrhy by měly podpořit marketingovou strategii společnosti a pomoci k dosažení firemních cílů.

The aim of this thesis is the proposal of amplification of marketing activities of the company. This work consist of the theoretical, analytical and practical parts. On the basis of findings of analysis are formulated particular proposals of amplifications of marketing activities in practical section. This proposals should give support to the company marketing strategy and help to achieve company aims.
The Proposal of Amplification of Marketing Activities of the Company
Keywords: Analýza; Cílový zákazník; Marketingová činnost; Marketing služeb; Marketingový výzkum; Přímý marketing; Analysis; Target customer; Marketing aktivity; Marketing of services; Marketing research; Direct marketing